Thermal Overload Relay Trainer Design for Electric Motor Control Practice - Ilham, Muhammad; Rizal Fachri, Muhammad; Baihaqi, Baihaqi (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2026)
The limited availability of adequate practical learning media often poses a significant challenge for students in understanding the applied principles of electrical components, particularly the Thermal Overload Relay (TOR). This study aims to design, develop, and evaluate the feasibility of a TOR trainer as an innovative learning medium for electric motor control practicum. The research methodology employed is Research and Development (R&D), adapting the 4D development model (Define, Design, Develop, Disseminate), which was limited to the development stage. Data were collected using Likert-scale validation instruments involving media and subject matter experts. The analytical results indicate that the TOR trainer obtained an average validation score of 4.2, categorized as "Highly Feasible." Specifically, the validity testing yielded a feasibility percentage of 93.5% for the media aspect and 91.35% for the material design aspect. These findings demonstrate that the developed TOR trainer possesses superior presentation quality and is highly representative for use as a supporting medium in practical activities. The implementation of this media is expected to enhance student comprehension effectiveness and the overall quality of the learning process in electric motor control systems within technical education environments